1987
DOI: 10.1002/ajmg.1320270213
|View full text |Cite
|
Sign up to set email alerts
|

Onset in the seventh decade and lack of symptoms in heterozygotes for the TTRMet30 mutation in hereditary amyloid neuropathy—type I (Portuguese, Andrade)

Abstract: In a Portuguese-American family with hereditary amyloid neuropathy (familial amyloidotic polyneuropathy), onset was in the seventh decade in all affected relatives. Another unusual characteristic was their origin from the Portuguese island of Madeira. In spite of this, the mutant transthyretin (TTRMet30) (the same variant prealbumin that is the circulating precursor of AFP protein in the classic Portuguese patients) could be found in the propositus' plasma. In addition, three other asymptomatic relatives (ages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…Previous work from our group also confirmed that late-onset and aged-asymptomatic carriers aggregate in families, and that, as in Sweden, isolated cases with late-onset often descend from aged-asymptomatic carriers 4 8 9…”
Section: Introductionsupporting
confidence: 79%
“…Previous work from our group also confirmed that late-onset and aged-asymptomatic carriers aggregate in families, and that, as in Sweden, isolated cases with late-onset often descend from aged-asymptomatic carriers 4 8 9…”
Section: Introductionsupporting
confidence: 79%
“…30 Yet, there are Portuguese asymptomatic carriers older than age 70 and as old as 90 years. 31 Similarly, asymptomatic individuals have been described in Japanese kindreds who were as old as 81 years and had serum levels of variant TTR as high as those with polyneuropathy. 32 In view of this, it is not surprising that the family history has been found to be negative in one third of Portuguese cases in patients with FAP 33 and in over half of patients with FAP from other ethnic backgrounds.…”
Section: Transthyretin Amyloidosismentioning
confidence: 95%
“…In other neuropathies, onset occurs during adulthood, as in some cases of CMT (more frequently for the axonal variety CMT2), and in FAP, where disease onset may be delayed until the 7 th decade of life [104].…”
Section: Age At Onsetmentioning
confidence: 99%